El plancton de Mar del Plata durante el período 1961-1962 (Buenos Aires, Argentina) - Balech, E. (1964)
The first part presents a general picture of the composition of the coastal plankton near Mar del Plata (Buenos Aires prov., Argentina) between August 1961-August 1962. Especially noted is the abundance of Noctiluca from October to the end of March. The second part deals with the plankton collected during a short cruise, named Operación Mar del Plata 1, planned to survey coastal waters. In the third part the author gives the descriptions of some new or interesting species. A chain-forming Gymnodinium is reported as G. catenatum; some differences with Graham description, could be due to the fact that he studied only preserved material. Oblea baculifera is a new species belonging to the new genus Oblea, of the Diplopsalis group, created for some species previ¬ously known as Peridiniopsis. A key of the included species is given. The other new species are Peridinium aspidiotum, P. anomaloplaxum, P. lipopodium and Gonyaulax fratercula, all of them carefully described and depicted. Sticholonche zanclea (Radiolaria), Calsiosolenia sinuosa (Coccolithophoridae) and Tintinnopsis levigata (Tintinnida) are reported for the first time in the South-Atlantic. For T. levigata ?, Balech, 1939, a new name has been created: T. tregouboffi. Some unknown details of the protoplasm of the silicoflagellate Dictyocha octonaria are described. In the fourth part the author compares the plankton taken in Mar del Plata with the previously studied at Pto. Quequén. The plankton of March-April points to an invasion of oceanic warm waters from the Brazilian Current System.